Konteks Budaya Gambar Binatang pada Seni Cadas di Sulawesi Selatan - Pasaribu, Yosua Adrian (Paradigma: Jurnal Kajian Budaya, 2016)
This article is based on a thesis with the same title on Archaeology Magister Program, Universitas Indonesia. This research relies on structuralist approach assuming that artists have potential choices to select motifs according to their artistic repertoire. That appropriate choices are guided by the site location in the region. Etnographic studies of animal motifs in rock art shows totemism, shamanism, and everyday life as cultural contexts. Based on that cultural contexts, it is known that shamanism was the cultural context of rock art in South Sulawesi which is dominated by one animal motif